Chart-to-text : a large-scale benchmark for chart summarisation - Leong, Tiffany Ko Rixie (Nanyang Technological University, 2021)
Charts are popularly used for communicating insights and exploring data. However, interpreting charts can be a challenging task. Automatically generated natural language summaries can help readers more easily understand charts by identifying the key insights.